Pregnancy complicated by arterial hypertension pathogenic factors, Lima, Peru, 1991-2006 - Pacora, Percy (2015)
OBJECTIVES: To determine pregnancy complicated by arterial hypertension pathogenic factors. DESIGN: Retrospective clinical study. SETTING: Hospital Nacional Docente Madre-Niño San Bartolome, Lima.PARTICIPANTS: Women with pregnancies complicated by arterial hypertension. INTERVENTIONS: The hospital’s perinatal information technology system was reviewed from January 1991 through December 2006 in order to determine the prevalence of pregnancies complicated by arterial hypertension, to establish associated factors and describe its natural history. MAIN OUTCOME MEASURES: Pregnancy arterial hypertension prevalence and conditioning factors. RESULTS: Pregnancy arterial hypertension prevalence was 8,6% (8 506/98 956). Preeclampsia and eclampsia represented 95% (8 085/8 506) of these cases, preeclampsia prevalence was 8,5% and eclampsia, 0,11%. Preeclampsia and eclampsia conditioning factors were: 1) vascular (100%); 2) hereditary (82%); 3) social (62,9%); 4) malnutrition (39,4%); 5) anatomical (33%); 6) metabolic (30,6%); 7) emotional (16%); and, 8) infectious (4%). CONCLUSIONS: Preeclampsia prevalence is higher in the nulliparous woman and in the multiparous mother with more than three children. Presence of clinical preeclampsia and/or eclampsia depends on the woman’s social situation, and severity, on gestational age and the existence of target organ harm in either maternal or fetal compartment.